2012
DOI: 10.1021/ac302542r
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Parameters for the Quantitative Surface-Enhanced Raman Scattering Detection of Mephedrone Using a Fractional Factorial Design and a Portable Raman Spectrometer

Abstract: A new optimization strategy for the SERS detection of mephedrone using a portable Raman system has been developed. A fractional factorial design was employed, and the number of statistically significant experiments (288) was greatly reduced from the actual total number of experiments (1722), which minimized the workload while maintaining the statistical integrity of the results. A number of conditions were explored in relation to mephedrone SERS signal optimization including the type of nanoparticle, pH, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 53 publications
1
72
0
1
Order By: Relevance
“…[33] More recently, a number of studies have evaluated the use of Raman for NPS products. [32,[34][35][36][37][38] Maheux and Copland (2011) used a range of analytical techniques including Raman spectroscopy for the identification of cathinones in seized samples. [34] Studies also reported on the use of Raman spectroscopy to discriminate between cathinone regioisomers [35] and derivatives [32] using benchtop Raman instruments employing a laser excitation wavelength (λ ex ) of 785 nm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[33] More recently, a number of studies have evaluated the use of Raman for NPS products. [32,[34][35][36][37][38] Maheux and Copland (2011) used a range of analytical techniques including Raman spectroscopy for the identification of cathinones in seized samples. [34] Studies also reported on the use of Raman spectroscopy to discriminate between cathinone regioisomers [35] and derivatives [32] using benchtop Raman instruments employing a laser excitation wavelength (λ ex ) of 785 nm.…”
Section: Introductionmentioning
confidence: 99%
“…[31,39,40] Goodacre and coworkers investigated the use of surface enhanced Raman spectroscopy (SERS) to enhance the Raman signal while also reducing interference due to fluorescence. [36,37] Although SERS is a viable approach for fluorescence reduction, careful and invasive sample preparation is often needed. An alternative approach which requires no sample preparation is the use of a longer λ ex (e.g., 1064 nm) which has been shown to improve identification of traditional drugs of abuse such as cocaine and amphetamine.…”
Section: Introductionmentioning
confidence: 99%
“…The colloid was assessed using UV-visible spectroscopy and scanning electron microscopy (SEM) and was very similar to that used in previously pub-lished studies. 25,26,34,35 Instrumentation Initial experiments were carried out to generate conventional Raman spectra of powdered codeine and codeine-d6, which were placed on a calcium fluoride (CaF2) disc and Raman spectra were recorded using 633 nm excitation (see ESI † for more details of the conventional Raman measurements). SERS spectra were recorded using a DeltaNu Advantage portable Raman spectrometer (DeltaNu, Laramie, WY, USA), equipped with a 633 nm HeNe laser emitting ∼3 mW on to the sample.…”
Section: Synthesis Of Silver Nanoparticlesmentioning
confidence: 99%
“…20 -24 Several studies have reported the application of SERS for the successful detection, identification and quantification of illicit drugs. 25,26 Alharbi and colleagues also used this approach for the quantitative detection of the opioid tramadol in artificial urine. 27 Dong et al employed (dynamic) D-SERS and support vector machines for the quanti-tative detection of methamphetamine in human urine.…”
Section: Introductionmentioning
confidence: 99%
“…48,49 Smith et al 50,51 provided an alternative to chromatography and proposed a novel sensing protocol based upon the electrochemical methods. 52,53 In this novel approach, the usually required thin metallic surface (typically gold or silver) was provided by galvanising a British two pence coin with silver. 50 Analysed in pH 4.3 acetate buffer, limits of detection were found to correspond to 11.80 μg mL −1 for 4-MMC and 11.60 μg mL −1 for 4-MEC.…”
Section: Usual Namesmentioning
confidence: 99%